Un lion nommé l’Americain - Rouch, Jean (France : Les Films de la Pléiade, 1972)
During the five years from 1957 to 1962, the crew followed the hunting campaigns of the Gow group from the village of Yatakala, led by the chief of hunters, Tahirou Koro. Discovery of the trail of a killer lion, "the American," who springs all of the traps of the hunters, who then kill two of his females. The first dies ritually, calmed by the praises of the hunter chief until the moment when she "vomits her death." But the second, "Fitili's lion," counterattacks and dangerously wounds a Peul herdsman before being paralyzed by the poison. So the victorious hunters, "tired but happy," return to their village, where they divide up the lion meat. And in the evening they tell their sons the marvelous story of gawey, gawey, the lion hunt. Introduction by Bernard Surugue.